The Relationship of Renal Resistive Index and Central Venous Pressure As Predictors of Acute Kidney Injury in Critically III Patients of Intensive Care Unit Adam Malik General Hospital Medan - Muhammad Apriandi Wira; Achsanuddin Hanafie; Asmin Lubis; Bastian Lubis (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2022)
Background: Changes in the doppler-based renal resistive index (RRI) occur prior to the changes of glomerular filtration rate (GFR) during the development of acute kidney injury (AKI) and during the healing process from AKI. Central venous pressure (CVP) is not only a marker for resuscitation, but also can determine the microcirculatory perfusion pressure as outflow obstruction.Objective: This study aims to determine the relationship between RRI and CVP as a predictor of AKI in critically ill patients admitted to the intensive care unit (ICU) of Adam Malik General Hospital.Methods: This was an observational study with prospective cohort design and diagnostic test method. This research was conducted at the Adam Malik General Hospital Medan from June to July 2020. Forty patients aging 18-65 years old who met the diagnostic criteria of sepsis and septic shock were examined for RI and CVP when admitted to the ICU.Results: RI had better sensitivity and specificity than CVP in predicting the incidence of AKI (sensitivity 68% vs 59%, specificity 77% vs 55.5%, Receiver operating characteristics (ROC) 0.870 vs 0.321 (95% confidence interval)).Conclusion: Based on the results of this study, the renal resistive index has better sensitivity and specificity than central venous pressure in predicting the incidence of AKI in critical patients in the ICU.